Optimasi Penggunaan Whatsapp Business Sebagai Sarana Pengembangan Pemasaran Produk Usaha Anggota PKK - Nova Tri Romadloni; Nisa Dwi Septiyanti; Rauhulloh Ayatulloh Khomeini Noor Bintang (Yayasan Literasi Sains Indonesia, 2023)
In realizing social welfare in terms of the economy, it starts from a small scope, namely the family. Where each family has a role as a PKK member, through this membership can provide training to market the products owned by each member so that they can overcome the problems that exist in the sale of products that are not well known to many people or have a less wide reach. This community service activity aims as an effort to increase knowledge and insight regarding digital marketing, especially focusing on using Whatsapp business so that it is more optimal in marketing products so that product sales results increase and increase family income. This activity was attended by PKK members Badran Mulyo, Lalung, Karanganyar. Some PKK members already have or already have WhatsApp accounts, but some others have not used WhatsApp specifically for business, namely Whatsapp business . The training is carried out using the devices of each member so that they can be directly applied to their respective businesses and products during the training. The results of the training were that PKK members were very enthusiastic about optimizing the use of whatsapp business as a media for product marketing, but in this training they still needed advanced training in aspects of creating whatsapp story content to make it more attractive to potential buyers.